Pelvic Inflammatory Disease (PID) Management in Corona Virus Disease 2019 (COVID-19) Pandemic Era - I Gde Sastra Winata; Musa Taufiq (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2021)
Objective: This article aims to review pelvic inflammatory disease management during the coronavirus disease 2019 pandemicMethod: We conducted a search for scientific articles through PubMed and Google Scholar, using the terminologies of “PID AND COVID-19”, “Pelvic Inflammatory Disease”; “Pelvic Inflammatory Disease AND COVID-19”, “PID Management AND COVID-19”, “Pelvic Inflammatory Disease Management AND COVID-19”, and “PID AND Pandemic” in English and Indonesian from 2019-2020.Result: There were a total of 25 scientific articles from PubMed and Google Scholar within 2019-2020 that were included as the source of this reviewConclusion: There is no difference between the management of pelvic inflammatory disease during and before the pandemic. The mode of medical services and follow up tends to be conducted virtually. Technology-based services for pelvic inflammatory disease during the corona virus disease 2019 pandemic are promising and have been proven to be an effective method, therefore virtual-based pelvic inflammatory disease services may be safely applied. However, if there is any indication of emergency found during the telemedicine services, a face-to-face consultation or emergency room visit should be recommended.Key words : COVID-19, Pelvic Inflammatory Disease, SARS-CoV-2Tatalaksana Radang Panggul selama Era Pandemi Virus Corona 2019 (COVID-19)AbstrakTujuan: Melakukan kajian mengenai tatalaksana dari penyakit radang panggul selama pandemi penyakit coronavirus 2019Metode: Kami melakukan pencarian artikel ilmiah melalui PubMed dan Google Scholar menggunakan terminologi “PID AND COVID-19”, “Pelvic Inflammatory Disease”; “Pelvic Inflammatory Disease AND COVID-19”, “PID Management AND COVID-19”, “Pelvic Inflammatory Disease Management AND COVID-19”, and “PID AND Pandemic” dalam Bahasa Inggris dan Indonesia dari tahun 2019-2020. Hasil: Ditemukan sebanyak 25 publikasi ilmiah dari pencarian di PubMed dan Google Scholar pada tahun 2019- 2020 yang digunakan sebagai sumber kajian ilmiah ini.Kesimpulan: Tatalaksana penyakit radang panggul sebelum dan selama pandemi tidak berubah. Metode pelayanan kesehatan dan follow up cenderung dilakukan secara virtual. Pelayanan kesehatan berbasis tekonologi untuk penyakit radang panggul selama pandemi penyakit coronavirus 2019 menjanjikan dan telah terbukti sebagai metode yang efektif, sehingga pelayanan kesehatan untuk penyakit radang panggul secara virtual dapat diaplikasikan secara aman. Jika ditemukan adanya indikasi kegawatdaruratan selama pelayanan telemedicine, pasien sebaiknya melakukan konsultasi tatap muka atau mengunjungi instalasi gawat darurat. Kata kunci: COVID-19, penyakit radang panggul, SARS-CoV-2